ISHANS AS SPIRITUAL LEADERS OF SUFI ORDERS IN CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article analyzes the eshens, who occupy an important place in the tariqas of the Central Asian region, as well as the origin and meaning of this term. In addition, based on historical sources, the study examines the spiritual leadership functions of eshens in the tariqas, their role in educating murids, their place in socio-religious life, and several issues related to the activities of the tariqas. It is emphasized that eshens played an important role in the spread of Islam in the region and in the formation of its spiritual culture.
Keywords: Ishan, tariqa, Sufism, murshid, murid, irshad, Central Asia, Islam, spiritual leadershi